Genome-Wide DNA Methylation Analysis of Hypothalamus During the Onset of Puberty in Gilts - Yuan, Xiaolong; Zhou, Xiaofeng; Chen, Zitao; He, Yingting; Kong, Yaru; Ye, Shaopan; Gao, Ning; Zhang, Zhe; Zhang, Hao; Li, Jiaqi (Frontiers in Genetics, 2019)
Although selection of the early age at puberty in gilts will make for a favorable effect on the reproductivity of sow, a large proportion of phenotypic variation in age at puberty of gilts can’t be explained by genetics. Previous studies have suggested that the hypothalamic DNA methylation exhibits a controlling role during the onset of puberty in mammals. However, the underling molecular mechanism regarding the regulation of the onset of puberty has remained largely unexplored in gilts. Herein, the genome-scale DNA methylation of hypothalamus was acquired, using the reduced representation bisulfite sequencing, to compare and describe the changes of DNA methylation across Pre-, In- and Post-pubertal gilts. In this study, the average methylation levels of CpGs and CpHs (where H= C, T or A) in CpG islands- and gene-related regions were gradually decreased in hypothalamic methylomes during the pubertal transition. Comparisons of Pre- vs. In-, In- vs. Post-, and Pre- vs. Post-pubertal stage revealed that there were 85726, 92914, and 100421 differentially methylated CpGs and 5940, 14804, and 16893 differentially methylated CpHs (where H= C, T or A) in the hypothalamic methylomes. The methylation changes of CpHs were more dynamic than that of CpGs, and methylation changes of CpGs and CpHs were likely to be respectively involved in the developmental processes of reproduction and the molecular processes of cellular communications in the hypothalamus. Moreover, methylation changes of CpHs were observed to overrepresent in the quantitative trait loci of age at puberty, and the biological function of these CpH methylation changes was enriched in the pancreas development in gilts. Furthermore, the mRNA levels of several differentially CpG or CpH methylated genes related to the transcription of RNA II polymerase, GnRH signaling pathway, Estrogen signaling pathway, PI3K-AKt signaling pathway, and Insulin signaling pathway, including MAX, MMP2, FGF11, IGF1R, FGF21 and GSK3B, were significantly changed across these pubertal stages in the hypothalamus. These results will help our understanding of how DNA methylation contribute to phenotypic variation of age at puberty.